Resource tax, Quality of Fishing Rights, and Economic Performance A comparative study of the fishing sectors in Iceland and Norway - Ólafsdóttir, Hallveig (UiT The Arctic University of Norway, 2021)
Property rights and economic performance have been highly linked concepts, where the former influence the latter. In this thesis, we seek to explore property rights as fishing rights in two large fishing nations, Norway and Iceland, and the economic performance of the fishing sectors. However, there is a fundamental difference between the fishing sector in Iceland and Norway. In Iceland, the government has implemented a resource tax on the fishing sector, while in Norway, there is no such similar resource taxation. As a matter of fact, Norway can be claimed to be an outlier by not introducing a resource tax, as opposed to three other countries located in the North-Atlantic; Greenland, the Faroe Islands, and Iceland. In these three countries, the use of resource tax has increased in the second decade of the century. Resource tax in Iceland has been formed as a mitigation tool or an answer to criticism from the public generated from increased profitability in the fishing sector. Increased profitability has been highly linked to a liberal uniform Individual transferrable quota (ITQ) system in Iceland. The ITQ system in Iceland reflects a fishing right that entails few restrictions and limitations on the operators. The objective of this thesis is twofold. Firstly, we will explore and compare the quality of fishing rights and economic performance in the two fishing nations, Iceland, and Norway. Secondly, we seek to determine whether the different resource taxation levels in Iceland and Norway can be explained by differences in the quality of fishing rights and economic performance.